Experimental study of film cooling over a fiber-reinforced composite plate with anisotropic thermal conductivity. (5th February 2019) - Tu, Zecan; Mao, Junkui; Han, Xingsi; He, Zhenzong
Highlights: Film cooling over a fiber-reinforced composite plate with anisotropic thermal conductivity was investigated experimentally. Variations of the anisotropic thermal conductivities' directions were considered. Both the average value and the uniformity of the cooling efficiencies were examined. Effects of the anisotropic thermal conductivities under different blowing ratios were discussed. Abstract: An experimental investigation was carried out to analyze the film cooling performance over a fiber-reinforced composite plate with anisotropic thermal conductivity (ATC). The influence of the ATC and its spatial variations on the cooling effect under different blowing ratios was studied. It was found that the heat transfer in the plate was enhanced in the direction with higher thermal conductivity. The average value and the uniformity of the cooling efficiency changed with different inclined angles between the directions of the ATC and the mainstream. The highest average cooling efficiency was achieved with different values of the stream-wise angle α and the span-wise angle β when different regions downstream of the film cooling were considered. For example, when the blowing ratio was equal to 0.5, the corresponding α and β for the highest average cooling efficiency in the downstream region (1D ≤ X ≤ 5D) were 60° and 0°, respectively. For the downstream region (0D ≤ X ≤ 10D), the corresponding α and β were 35° and 60°, respectively. When the blowing ratio was different, the affected laws of α and β also exhibited variations.